Perencanaan Sistem Pengelolaan Air Limbah Domestik Terpusat (SPALD-T) di Kelurahan Kujangsari, Kota Bandung - Halomoan, Nico; Barri, Defa Abdul (Jurnal Serambi Engineering, 2026)
Kujangsari Village is classified as an urban slum area located in Bandung Kidul District, Bandung City, with a total area of 1.3 km². Therefore, Kujangsari Village requires planning for a Domestic Wastewater Management System. One of the things that needs to be done is to solve the problem of domestic wastewater distribution by planning a Domestic Wastewater Management System (SPALD). Initial analysis shows that Kujangsari Village is suitable for service with a centralized SPALD at the settlement scale based on considerations of achieving safe sanitation quality. The planning was conducted by considering technical and financial aspects. Technical aspects include wastewater flow rate calculations, pipe dimensions, wastewater flow velocity, pipe excavation, wastewater treatment plant (WWTP) dimensions, and technical planning drawings. Financial aspects include the costs of constructing the wastewater collection and treatment system. The results of the centralized DWMS planning for Kujangsari Village indicate that the designed system will serve a population of 41,142 people with a pipeline network of 19,410 meters in length, utilizing pipes with diameters ranging from 110 to 267 milimeters. The wastewater will be treated in an Anaerobic Baffled Reactor (ABR) WWTP with a capacity of 7,345.24 m³/day. The estimated planning cost is IDR 15,812,591,574, with details of IDR 9,185,967,724 for domestic wastewater distribution and IDR 6,626,623,850 for the construction of the ABR wastewater treatment plant.